Delimiting cross-border areas - Medeiros, E. (LISER Tuesday Seminars, 2019)
The presentation subject results from my experience in working with the European Commission in assessing European Territorial Cooperation related programmes, and the need to identify the optimal cross-border area for the INTERREG-A programmes. Hence, it proposes a conceptual approach to delimit these areas, which can be applied not only in Europe, but also internationally. In essence, the presentation will discuss the concept of border area by identifying a number of factors which should be considered when delimiting cross-border areas for policy implementation (CBAPI). These include historical, spatial, demographic, cultural, data, institutional, economic, infrastructural and environmental factors. The relevance of this debate for the border studies is twofold. Firstly, it covers a void in existing literatures, thus adding a valuable conceptual contribution to the delimitation of cross-border areas. Secondly, it provides a concrete theoretical platform for interested entities such as the European Commission to appropriately delimit CBAPI, for programmes like the INTERREG-A. A concrete example on how to implement the proposed methodology will be presented.